John J. Pershing - McNeese, Tim; Weinberger, Caspar W. (Philadelphia : Chelsea House Publishers, 2004)
Reviews the life and battles of General "Black Jack" Pershing, who had more than thirty years of field experience when he was tapped to lead the American Expeditionary Forces during World War I.
"Cool as a bowl of cracked ice" -- Missouri born and raised -- In the Army -- Action in Cuba -- Assignments in paradise -- A punitive expedition -- "Lafayette, we are here" -- Into the woods.
Grade level : 7 - 9
Keywords: Pershing, John J. -- 1860-1948; United States. -- Army; Generals -- United States; Generals; United States -- History, Military -- 20th century